Governance Collaborative Management for Handling Stunting in Bone District - Sudiarti Dewi Kurra; Henni Zainal; Dewi Sulfa Saguni (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
To obtain superior Human Resources (HR) is still a challenge in various countries. Health and education are the focus of the main problems that hinder the achievement of superior human resources. Millions of young children are still not reaching their full potential due to a lack of nutrition, learning, and stimulation as well as exposure to stress. Bone Regency is one of the districts in South Sulawesi with a relatively high stunting rate. Bone Regency ranks 4th as a district with a high prevalence of stunting out of 24 districts in South Sulawesi after Jeneponto, Maros, Takalar. Bone Regency is one of the regencies that has been the location for stunting management interventions since 2019, considering that the stunting rate in Bone Regency is quite high. The purpose of this study was to analyze the intervention of the government, in this case stakeholders, non-governmental organizations, communities and the private sector, to collaborate to solve the problem of stunting in Bone district. One of the keys to effective collaborative governance requires governance structures and processes that facilitate coordination and decision-making across sectors. The data collection method was carried out through in-depth interviews and focus group discussions involving stakeholders at the provincial and district levels, to program implementers at the community level - sub-districts/community health centers (puskesmas) and villages/kelurahans. In-depth interviews with stakeholders at the provincial and district levels whose fields of work are related to programs/activities related to stunting prevention. So that the research results can describe the Electronic Based Government System (SPBE) in realizing active collaboration between stakeholders in the following years